Processing Coconut (Cocos Nucifera L.) into Virgin Coconut Oil Products: Cold-press Method - Peter Dekker; Hanny Frederik; Ivan Th. J. Weismann (Khaliya Onomiyea: Jurnal Abdimas Nusantara, 2023)
This article will describe the impact producing and using Virgin Coconut Oil can make on the life of people in a small village. It offers them work opportunities and a better income for the farmers, but it also helps them become healthier. It has a reason why people worldwide described the Coconut as the “fruit of life”. The method is a literature review and describes the processing of Virgin Coconut Oil located in Takalar, South Sulawesi, Indonesia. Sulalam's VCO has a good impact on body health and for maintaining health.